Effect of planting date and nitrogen level on growth and yield of tropical cauliflower (Brassica oleracea convar botrytis var botrytis) - SINGH, J P; SINGH, M K; SINGH, R D (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1990-91 and 1991-92 to study the response of cauliflower [Brassica oleracea L. convar batrytis (L.) Alef. var botrytis L.) to transplanting date and nitrogen level in an alkaline soil, The nutrient status of the experimental field showed deficiency of nitrogen (106 kgÂ N/ha), Transplanting date, nitrogen level and cultivar showed significant effect on the curd yield, leaves/plant, plant height, gross weight and net curd wcight/plant, All increase in N from 100 to 200 kg/ha increased the yield of marketable produce from 9,62 to 13.99 tonnes/ha as well as the weight ofÂ individualÂ curd from 404,53 to 537,89 g/plant. The cultivar ’Narendra Gobhi 1’ recorded the higher yield (12.5 tonnes/ha) when transplanted in September than when transplanted in October.